2021
DOI: 10.1002/mus.27223
|View full text |Cite
|
Sign up to set email alerts
|

The Spinal Muscular Atrophy Health Index: A novel outcome for measuring how a patient feels and functions

Abstract: Introduction:The Spinal Muscular Atrophy Health Index (SMA-HI) is a multifaceted, disease-specific, patient-reported outcome to measure an SMA patient's perception of their disease burden. In preparation for upcoming therapeutic trials, we examine the validity, reliability, and usability of the SMA-HI in adults, teenagers, and children with SMA.Methods: Using data from a cross-sectional study of 359 international adult patients with SMA, we identified the most relevant symptoms to include in the SMA-HI. We uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 10 publications
(22 reference statements)
1
27
2
Order By: Relevance
“…As in previously published studies, 9,10 results of the current analysis confirm that SMA‐HI scores increase with increasing disease severity. In the previous cross‐sectional study involving 359 adults with SMA (mean age = 42 y; range, 18–81 y), the results were stratified by age group (18 to <42 y vs ≥42 y).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As in previously published studies, 9,10 results of the current analysis confirm that SMA‐HI scores increase with increasing disease severity. In the previous cross‐sectional study involving 359 adults with SMA (mean age = 42 y; range, 18–81 y), the results were stratified by age group (18 to <42 y vs ≥42 y).…”
Section: Discussionsupporting
confidence: 91%
“…In the previous cross-sectional study involving 359 adults with SMA (mean age = 42 y; range, 18-81 y), the results were stratified by age group (18 to <42 y vs ≥42 y). Compared with these older-age cohorts, 9 results from the current study found that younger populations (aged 12-25 y) generally had lower SMA-HI total and subscale scores. 9 This finding may suggest an association between older individuals with SMA, higher disease burden, and increased SMA-HI scores.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Besides, they do not represent motor functions not related to the extremities like swallowing which are nevertheless important for the patients' QoL. Recently, the Spinal Muscular Atrophy Health Index (SMA-HI) has been proposed as a novel means to capture the disease burden from a patient's perspective ( 36 ). Apart from that, treatment expectations have been shown to be even higher in less severely affected individuals ( 37 ), and other individual psychological factors ( 38 ) might have influenced the patient-reported QoL in our study.…”
Section: Discussionmentioning
confidence: 99%
“…PedsQL Neuromuscular Module [ [70]], Assessment of Caregiver Experience in Neuromuscular Disease (ACEND) [21], Pediatric Evaluation of Disability Inventory-Computerized Adaptive Testing (PEDI-CAT) [22]. Recent advances include the development of the SMA Health Index, a novel scale developed for use in Types 2 and 3 SMA [ [69]], but it does not directly assess independence.…”
Section: Introductionmentioning
confidence: 99%